Pituitary Sarcoidosis in a Pediatric Patient Successfully Treated With Adalimumab and Methotrexate - D. Sofia Villacis-Nunez MD; Amit Thakral MD (SAGE Publishing, 2021)
Neurosarcoidosis is a rare phenomenon in the pediatric population, with only a few cases reported in the literature worldwide. While hypothalamo-pituitary involvement is known to occur, direct infiltration of the pituitary gland and isolated anterior pituitary dysfunction without diabetes insipidus is seldom observed. A high index of suspicion is required for diagnosis of neurosarcoidosis, and treatment can be challenging due to lack of standardized guidelines. We present the case of a 17-year-old female with known sarcoidosis of the lacrimal glands, who developed severe headache and neurologic symptoms secondary to granulomatous infiltration of the pituitary gland and infundibulum due to neurosarcoidosis. She was successfully treated with corticosteroids, methotrexate, and adalimumab, with complete radiologic resolution. This is the first documented pediatric case of neurosarcoidosis with radiologic granulomatous infiltration of the pituitary gland, manifesting as partial anterior hypopituitarism, in the form of central hypothyroidism, without diabetes insipidus.